2021
DOI: 10.1016/j.resuscitation.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Finding alternative sites for intraosseous infusions in newborns

Abstract: Aim: Intraosseous (IO)-access plays an alternative route during resuscitation. Our study in preterm and term stillborns was performed to find alternative IO puncture sites beside the recommended proximal tibia. Methods:The cadavers used were legal donations. 20 stillborns (mean: 29.2weeks, IQR 27.1À39.6) were investigated. Spectral-CT were analysed to calculate the diameter and circumferences of: i) proximal humerus ii) distal femur iii) proximal tibia iv) diaphyseal tibial. Contrast medium was applied under v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…The mean (median) diameter of the proximal tibia at the most suitable puncture site was 8.4 mm (8.3) (transverse) and 9.2 mm (9.2) (anterior-posterior) in the 3000-4000 g weight group. These diameters are slightly larger than those reported by Suominen et al (7.4 mm transverse and 7.7 mm anterior-posterior diameter, assessed by X-ray) [5] and Tonder et al (7.1 mm transverse and 7.7 mm anterior-posterior) [3], and smaller than those reported by Eifinger et al, who found an average diameter of 12.0 mm at the proximal tibia [7]. These differences may be a result of the selected measurement technique (i.e., X-ray or computer tomography vs. ultrasound) but also, compared to Eifinger et al, the site of measurement differed.…”
Section: Tibial Dimensionscontrasting
confidence: 63%
See 2 more Smart Citations
“…The mean (median) diameter of the proximal tibia at the most suitable puncture site was 8.4 mm (8.3) (transverse) and 9.2 mm (9.2) (anterior-posterior) in the 3000-4000 g weight group. These diameters are slightly larger than those reported by Suominen et al (7.4 mm transverse and 7.7 mm anterior-posterior diameter, assessed by X-ray) [5] and Tonder et al (7.1 mm transverse and 7.7 mm anterior-posterior) [3], and smaller than those reported by Eifinger et al, who found an average diameter of 12.0 mm at the proximal tibia [7]. These differences may be a result of the selected measurement technique (i.e., X-ray or computer tomography vs. ultrasound) but also, compared to Eifinger et al, the site of measurement differed.…”
Section: Tibial Dimensionscontrasting
confidence: 63%
“…Finally, it must be emphasized that this study only investigated the tibia as an option for IO access, which seems to be the most commonly selected site for IO access in neonatal and pediatric resuscitation [4,11], to date. Nonetheless, alternative puncture sites, such as the proximal humerus or distal femur, have been discussed [7] and should be further investigated.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An indentation the predominant puncture site used in this analysis was the proximal tibia (96%), but other sites (distal tibia, distal femur, and proximal humerus) were also chosen. Eifinger et al recently analyzed alternative sites for IO access in stillborn neonates and suggested the proximal humeral head as well as the distal femoral end as possible further puncture sites in neonates ( 18 ). Clearly, future studies are required to compare different puncture sites and success rates in the neonatal population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in infants, the distal tibia may be also selected. More recently, the superolateral aspect of the humerus and distal femoral end have been considered as an alternative IO site in newborns [ 7 ]. In inserting the IO needle, care must be taken in infants and young children to avoid the epiphyseal plates.…”
mentioning
confidence: 99%